Depositional age, provenance and metamorphic age of metasedimentary rocks from southern Madagascar - Collins, A.; Kinny, Peter; Razakamananad, T. (Elsevier Science BV, 2011)
Southern Madagascar is the core of a > 1 million km2 Gondwanan metasedimentary belt that forms much of the southern East African Orogen of eastern Africa, Madagascar, southern India and Sri Lanka. Here the Vohibory Series yielded U–Pb isotopic data from detrital zircon cores that indicate that it was deposited in the latest Tonian to late Cryogenian (between ~ 900 and 640 Ma). The deposition of the Graphite and Androyen Series protoliths is poorly constrained to between the late Palaeoproterozoic and the Cambrian (~ 1830–530 Ma). The Vohibory Series protoliths were sourced from very restricted-aged sources with a maximum age range between 910 and 760 Ma. The Androyen and Graphite Series protoliths were sourced from Palaeoproterozoic rocks ranging in age between 2300 and 1800 Ma. The best evidence of the timing of metamorphism in the Vohibory Series is a weighted mean 206Pb/238U age of 642 ± 8 Ma from 3 analyses of zircon from sample M03-01. A considerably younger 206Pb/238U metamorphicage of 531 ± 7 Ma is produced from 10 analyses of zircon from sample M03-28 in the Androyen Series. This ~ 110 Ma difference in age is correlated with the early East African Orogeny affecting the west of Madagascar along with its type area in East Africa, whereas the Cambrian Malagasy Orogeny affected the east of Madagascar and southern India during the final suturing of the Mozambique Ocean.